Pendidikan Literasi Politik Untuk Siswa SMA Negeri 25 Kabupaten Banyuasin - Isyanawulan, Gita; Yulasteriyani; Hendarso, Yoyok (Nawadeepa: Jurnal Pengabdian Masyarakat, 2023)
Political Literacy Education for students at SMA Negeri 25 Banyuasin is an important tool or media to help socialize the importance of political education for the millennial generation. The activities carried out are in the form of outreach about political education, as well as the importance of using digital literacy in obtaining political information for students. This activity is carried out to provide knowledge transfer and is expected to be able to provide enthusiasm for students as first-time voters to participate actively in the upcoming elections and post-conflict local elections. However, the problems faced by Banyuasin 25 Public High School students who already have voting rights include: (1) There are still students who don't care about politics so they tend to be apathetic in the election process. In addition, ignorance of information related to politics and elections causes students to join abstentions; (2) There are students who use their voting rights in selecting candidate pairs based on the amount of money they get (money politics); (4) There are students who do not know how to use social media properly and wisely. The results obtained after socialization include: (1) Many students access social media in the form of Facebook to obtain information about politics, and most of those who use Facebook are female students; and (2) most of the students also get their political knowledge through social media, so it is necessary to have the role of the family and school so that students get correct and reliable information about political education. Therefore, the objectives of this community service activity are: (1) To be able to increase students' understanding of politics, especially in the current digital era; (2) increasing students' interest in political literacy education; (3) Improving student values/norms and character, especially with regard to good and wise use of social media.